Pengembangan kurikulum pendidikan keagamaan Islam di Mesjid Istiqlal Houston, Texas USA - Indriya; Fauziah, Fuja; Husna, Miftachul; Maulidina, Azzahra; AG, Moh Satryo (LPPM Universitas Ibn Khaldun, Bogor, 2024)
This research aims to develop an Islamic religious education curriculum to strengthen the faith. This study focuses on how the development of the Islamic religious education curriculum in Madrasas strengthens the faith and forms Islamic character, especially for children and teenagers in the Indonesian Muslim community at the Houston, Texas Mosque, United States. This search uses a descriptive method with a qualitative approach. Observation techniques and in-depth interviews were used to collect data and search for previous articles. The results of this research show, first, that the development of the PAI curriculum at Madrasah Istiqlal Quranic School (IQS) contributes to strengthening the aqidah of students. Second, Islamic Religious Education is very influential and contributes to the formation of Islamic character as the main capital in the development and strength of Islam in the American Union. Even though the fulfillment of spiritual needs is still very limited, with the capital of enthusiasm, belief, and strong desire, as an effort to strengthen the faith and form Islamic character everywhere, thirdly, the habit of reading and practicing cleanliness of the heart is a culture in Madrasas. AbstrakPenelitian ini bertujuan untuk mengembangkan kurikulum pendidikan keagamaan Islam dalam penguatan aqidah. Kajian ini berfokus pada bagaimana pengembangan kurikulum pendidikan keagamaan Islam di Madrasah dalam penguatan aqidah dan pembentukan karakter Islami, khususnya pada anak-anak dan remaja komunitas muslim Indonesia di Mesjid Houston Texas Amerika Serikat. Penelusuran ini menggunakan metode deskriptif, dengan pendekatan kualitatif. Teknik pengamatan, wawancara mendalam digunakan untuk pengumpulan data, dan juga penelusuran berbagai artikel sebelumnya. Hasil penelitian ini menunjukkan, pertama, pengembangan kurikulum PAI di Madrasah Istiqlal Quranic School (IQS) berkontribusi pada penguatan aqidah para peserta didik, kedua, Pendidikan Agama Islam sangat berpengaruh dan berkontribusi pada pembentukan karakter Islami sebagai modal utama dalam pengembangan, dan kekuatan Islam di Amerika Serikat. Walau pemenuhan kebutuhan rohaniah memang masih sangat terbatas, namun dengan modal semangat, keyakinan, dan keinginan yang kuat, sebagai upaya dalam membentuk penguatan aqidah dan pembentukan karakter Islami dimanapun, ketiga, pembiasaan membaca dan melatih kebersihan hati merupakan budaya di Madrasah.